SELF-EFFICACY AND SELF-REGULATION WITH ACADEMIC PROCRASTINATION IN MUSLIM ADOLESCENTS DURING THE ONLINE LEARNING PERIOD - Syapira, Syilma Aulia; Budiman, Budiman; Selamat, Mohd Nasir (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study aims to determine the relationship between self-efficacy and self-regulation with academic procrastination in Muslim adolescents during online learning. The research method used in this research is correlational quantitative. The subjects of this study were Muslim adolescents in one of the public high schools in Palembang. The sample of this study was 298 people taken by quota sampling technique. The instruments used are the self-efficacy, self-regulation, and academic procrastination scale. The results of data analysis with multiple regression analysis (assisted by SPSS version 26) showed that there was a significant relationship between self-efficacy and self-regulation with academic procrastination in online learning (Y = 237.034 + - 0.427X1 + - 0.241X2); (p<0.05) so that the research hypothesis is accepted with the effective contribution of X1 and X2 simultaneously on academic procrastination by 27%, while other variables outside this study influence the remaining 73%. Self-efficacy and self-regulation were negatively and significantly associated with academic procrastination in online learning (rx1 = -0.420; rx2= -0.400; p<0.05). It means that when the level of self-efficacy and self-regulation is high, the level of academic procrastination tends to be below. Conversely, when the level of self-efficacy and self-regulation is low, the level of academic procrastination tends to be high.